Ultrahigh water and oxygen barrier film for vehicle-mounted OLED display product

By designing a multi-layered barrier membrane, using the bilayer structure and hydrogen bonding of phospholipid vesicles formed by cholesterol and phospholipids, the problem of the barrier membrane of existing OLED display products is solved, and efficient water and oxygen barrier is achieved and self-repairing, suitable for on-board OLED display products.

CN119489609AInactive Publication Date: 2025-02-21SUZHOU ZIJIN PLASTIC

Patent Information

Application Number
CN202510072205.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The barrier film of existing OLED display products is extremely sensitive to water and oxygen, which can easily lead to device functions degradation and failure, and insufficient impact and thermal stability performance, making it difficult to meet the high barrier requirements of automotive OLED display products.

Method used

An ultra-high water oxygen barrier film for automotive OLED display products is designed, with a thickness of 15-35μm, including a multi-layer structure: the first antistatic layer, the first barrier layer, the OLED working layer, the second barrier layer, and the polyterephthalene Ethylene dicarboxylate layer and second antistatic layer. The barrier layer uses cholesterol and phospholipids to form a bilayer structure of phospholipid vesicles, and through hydrogen bonding between N-acryloylglycine and graphene oxide, a multiple hydrogen bond structure is formed to improve barrier performance and self-healing properties.

Benefits of technology

It significantly improves the water-to-oxidity and service life of the water-to-oxidity barrier film, enhances the tensile strength and thermal stability of the film layer, and is suitable for various OLED flexible panels. It has a simple structure and is easy to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489609A_ABST
    Figure CN119489609A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of barrier films, and particularly discloses an ultrahigh water and oxygen barrier film for a vehicle-mounted OLED display product. The thickness of the ultrahigh water and oxygen barrier film is 15-35 microns, and the ultrahigh water and oxygen barrier film sequentially comprises a first antistatic layer, a first barrier layer, an OLED working layer, a second barrier layer, a polyethylene glycol terephthalate layer and a second antistatic layer, the thickness ratio of the first antistatic layer to the first barrier layer to the OLED working layer to the second barrier layer to the polyethylene glycol terephthalate layer to the second antistatic layer is (2-4): (2-4): (8-16): (2-4): (4-8): (2-4). The first barrier layer and the second barrier layer are prepared from the following raw materials in parts by mass: 1-2 parts of cholesterol, 5-15 parts of phospholipid, 1-2 parts of N-acryloyl glycinamide, 1-2 parts of graphene oxide, 0.01-0.1 part of a photoinitiator, 1-2 parts of hydroxypropyl methyl cellulose, 1-5 parts of fluorinated ethylene propylene, 1-5 parts of tetra-n-butyl titanate and 1-2 parts of a surfactant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of barrier films, and in particular to an ultra-high water and oxygen barrier film for vehicle-mounted OLED display products. Background Art

[0002] High barrier refers to extremely low permeability to low molecular weight chemicals. Currently, high barrier is one of the characteristics required of many polymer materials. High barrier materials can effectively maintain the original performance of the product and extend the product life. High barrier films have broad application prospects in the fields of electronic circuits, biomedicine, environmental protection, medical care, etc. As a new generation of ideal display devices, OLED has excellent characteristics such as self-luminescence, wide viewing angle, low power consumption, high contrast, large-area film formation, and rapid response. It has broad application prospects in the world's high-end TVs, mobile phone screens, smart lighting and other fields.

[0003] Since OLED is very sensitive to water vapor in the air, the presence of water vapor is the main factor affecting the life of OLED devices. Most plastic substrates are not able to fully block the intrusion of foreign impurities, liquids and gases. The metal cathode used in OLED devices is generally aluminum, magnesium, calcium and other active metals, which are very easy to react with the infiltrated water vapor, affecting the injection of charge. In addition, the infiltrated water and oxygen will also react chemically with the organic light-emitting materials, and these reactions will cause the performance of the device to decline.

[0004] At present, the packaging methods of flexible OLED devices are usually multi-layer thin film composite packaging structure and single-layer thin film packaging structure. The multi-layer thin film composite packaging structure uses multi-layer thin film coating and sealing, which affects the light transmittance; although the single-layer thin film packaging structure can effectively reduce the water and oxygen permeability, it is easy for the barrier layer of flexible OLED devices to crack, which aggravates the water and oxygen penetration. Although one or several layers of thin film can be deposited on OLED to isolate external water and oxygen, it has poor mechanical resistance. Once the surface is slightly scratched, it is very easy to cause barrier failure.

[0005] At present, OLED barrier films are extremely sensitive to water and oxygen. Defects such as pixel blackening and accumulation caused by water and oxygen leakage and interface diffusion can easily lead to device functional degradation and failure. Currently, OLEDs are required to have a lifespan of 10,000 hours, and the water vapor transmission rate (WVTR) of the encapsulation film must be less than 10 -5 g / (m 2 •d), oxygen transmission rate is less than 10 -3 mL / (m 2 •d•0.1MPa), which has extremely high barrier requirements. At the same time, the existing barrier films have insufficient impact resistance and thermal stability, and are very likely to cause damage to the OLED screen during use, which needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an ultra-high water and oxygen barrier film for vehicle-mounted OLED display products.

[0007] The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 15-35μm and comprises in sequence: a first antistatic layer, a first barrier layer, an OLED working layer, a second barrier layer, a polyethylene terephthalate layer, and a second antistatic layer; the thickness ratio of the first antistatic layer, the first barrier layer, the OLED working layer, the second barrier layer, the polyethylene terephthalate layer, and the second antistatic layer is 2-4:2-4:8-16:2-4:4-8:2-4.

[0008] Preferably, the raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and antistatic agent; the mass ratio of linear low-density polyethylene, low-density polyethylene and antistatic agent is 40-50:50-60:1-2.

[0009] More preferably, the antistatic agent is ethoxylated alkyl amide or / and ethoxylated lauryl amide.

[0010] Preferably, the raw materials of the first barrier layer and the second barrier layer include, by mass, 1-2 parts of cholesterol, 5-15 parts of phospholipids, 1-2 parts of N-acryloylglycinamide, 1-2 parts of graphene oxide, 0.01-0.1 parts of photoinitiator, 1-2 parts of hydroxypropyl methylcellulose, 1-5 parts of polyperfluoroethylene propylene, 1-5 parts of tetrabutyl titanate, and 1-2 parts of surfactant.

[0011] Preferably, the first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Add cholesterol and phospholipids to chloroform and stir evenly, remove chloroform by rotary evaporation, add to deionized water and disperse evenly, add N-acryloyl glycinamide and graphene oxide, ultrasonically disperse for 10-30 minutes, add photoinitiator, ultraviolet irradiation for 20-40 minutes, high-pressure microfluidization treatment for 2-4 times, and vacuum dry to obtain pretreated graphene; S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and surfactant to an ethanol aqueous solution, adjust the pH value of the system to 3-5, perform ultrasonic treatment for 1-2 hours, spray on the substrate using a spray gun, roll after drying, bake at 120-140°C for 10-15 seconds, remove the substrate, and cool to room temperature.

[0012] More preferably, in S1, the ultrasonic frequency is 5-12 kHz.

[0013] More preferably, in S1, the pressure of the high-pressure microfluidization treatment is 6.895-34.475 MPa.

[0014] More preferably, in S1, the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0015] More preferably, in S2, the surfactant is sodium dodecyl sulfate.

[0016] More preferably, in S2, the ultrasonic frequency is 5-12 kHz.

[0017] More preferably, in S2, the substrate material is polystyrene.

[0018] More preferably, in S2, the particle size of the polyperfluoroethylene propylene is 1-15 μm.

[0019] Beneficial effects: In the present invention, barrier layers are arranged between the first antistatic layer and the OLED working layer, and between the OLED working layer and the PET layer, which can not only improve the water and oxygen barrier properties of the barrier layer and increase the service life of the entire water and oxygen barrier film, but also cooperate with the antistatic layer and the PET layer to make the obtained product structure extremely stable, suitable for various OLED flexible panels, simple in structure, and easy to use.

[0020] In the barrier layer used in the present invention, cholesterol and phospholipids are used to form a phospholipid vesicle double-layer structure, and N-acryloyl glycinamide and graphene oxide are bonded to the hydrophilic outer layer of the double-layer structure through hydrogen bonds. After initiation, the two are combined in the outer layer of the phospholipid vesicle, which not only has good barrier performance and effectively reduces the influence of water vapor and oxygen, but also the multiple hydrogen bond structures formed after the combination can make the barrier layer have good self-healing properties. The thin film formed by spraying on the substrate with a spray gun can be effectively wrinkled after rolling and heating, which can cooperate with the effect of silica particles to achieve a significant superhydrophobic effect.

[0021] Experiments have found that the barrier film formed by the barrier layer and other multi-layer structures used in this application not only has good moisture resistance and excellent super-hydrophobic properties, but also has good self-repairing effect and can effectively maintain a high barrier state. In addition, the film layer has high tensile strength and good thermal stability, which can significantly enhance the dimensional stability of the product.

[0022] The present invention adds a barrier layer to the organic layer, which can not only significantly prolong the permeation path and permeation time of water and oxygen molecules in the barrier layer, but also the nanoparticles and the stable pleated structure have excellent moisture barrier effect, and the super-hydrophobic structure layer can exist stably with excellent barrier performance. The present invention effectively improves the production efficiency and the water and oxygen barrier properties of the composite film layer, significantly enhances the service life of the entire water and oxygen barrier film, and has good self-repairing effect and excellent mechanical properties. It is suitable for various OLED flexible panels, has a simple structure, and is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the structure of the ultra-high water and oxygen barrier film for the vehicle-mounted OLED display product proposed by the present invention. Among them, 1 is the first antistatic layer, 2 is the first barrier layer, 3 is the OLED working layer, 4 is the second barrier layer, 5 is the polyethylene terephthalate layer, and 6 is the second antistatic layer.

[0024] Figure 2 This is a comparison chart of the barrier properties of the ultra-high water and oxygen barrier films for vehicle-mounted OLED display products obtained in Example 5 and Comparative Examples 1-3.

[0025] Figure 3 This is a comparison chart of the static water contact angle and tensile strength of the ultra-high water and oxygen barrier films for vehicle-mounted OLED display products obtained in Example 5 and Comparative Examples 1-3.

[0026] Figure 4 This is a comparison chart of the thermal stability of the ultra-high water and oxygen barrier films for vehicle-mounted OLED display products obtained in Example 5 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0027] The present invention will be further explained below in conjunction with specific embodiments.

[0028] Example 1 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 15μm and includes: a first antistatic layer with a thickness of 1.5μm, a first barrier layer with a thickness of 1.5μm, an OLED working layer with a thickness of 6μm, a second barrier layer with a thickness of 1.5μm, a polyethylene terephthalate layer with a thickness of 3μm, and a second antistatic layer with a thickness of 1.5μm.

[0029] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated alkyl acid amine; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated alkyl acid amine is 40:50:1.

[0030] The raw materials of the first barrier layer and the second barrier layer include: 1g of cholesterol, 5g of phospholipids, 1g of N-acryloylglycinamide, 1g of graphene oxide, 0.01g of 1-hydroxycyclohexylphenyl ketone, 1g of hydroxypropyl methylcellulose, 1g of polyperfluoroethylene propylene, 1g of tetrabutyl titanate, and 1g of sodium dodecyl sulfate.

[0031] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Cholesterol and phospholipids were added to 10 g of chloroform and stirred evenly. The chloroform was removed by rotary evaporation. The mixture was added to 20 g of deionized water and dispersed evenly. N-acryloyl glycinamide and graphene oxide were added. The mixture was ultrasonically dispersed for 10 min at an ultrasonic frequency of 5 kHz. 1-hydroxycyclohexyl phenyl ketone was added. The mixture was ultraviolet-irradiated for 20 min. The mixture was treated with 6.895 MPa high-pressure microfluidizer for 2 times and vacuum-dried to obtain pretreated graphene. S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 20 g of 40% ethanol aqueous solution, adjust the pH value of the system to 3-5, ultrasonically treat for 1 hour, and the ultrasonic frequency is 5 kHz. Use a spray gun to spray on a polystyrene substrate, roll it after drying, and send it into a convection oven. Bake it at a temperature of 120°C for 10 seconds, remove the polystyrene substrate, and cool it to room temperature.

[0032] Example 2 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 35μm and includes: a first antistatic layer with a thickness of 3.5μm, a first barrier layer with a thickness of 3.5μm, an OLED working layer with a thickness of 14μm, a second barrier layer with a thickness of 3.5μm, a polyethylene terephthalate layer with a thickness of 7μm, and a second antistatic layer with a thickness of 3.5μm.

[0033] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated alkyl acid amine; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated alkyl acid amine is 50:60:2.

[0034] The raw materials of the first barrier layer and the second barrier layer include: 2g cholesterol, 15g phospholipid, 2g N-acryloylglycinamide, 2g graphene oxide, 0.1g 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, 2g hydroxypropyl methylcellulose, 5g polyperfluoroethylene propylene, 5g tetrabutyl titanate, and 2g sodium dodecyl sulfate.

[0035] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Cholesterol and phospholipids were added to 20 g of chloroform and stirred evenly. The chloroform was removed by rotary evaporation. The mixture was added to 40 g of deionized water and dispersed evenly. N-acryloyl glycinamide and graphene oxide were added. The mixture was ultrasonically dispersed for 30 min at an ultrasonic frequency of 12 kHz. 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone was added. The mixture was irradiated with ultraviolet light for 40 min. The mixture was treated with a high-pressure microfluidizer at 34.475 MPa for 4 times and vacuum dried to obtain pretreated graphene. S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 30 g of 60% ethanol aqueous solution, adjust the pH value of the system to 3-5, ultrasonically treat for 2 hours, and the ultrasonic frequency is 12 kHz. Use a spray gun to spray on a polystyrene substrate, roll it after drying, and send it into a convection oven. Bake it at a temperature of 140°C for 15 seconds, remove the polystyrene substrate, and cool it to room temperature.

[0036] Example 3 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 20μm and includes: a first antistatic layer with a thickness of 2μm, a first barrier layer with a thickness of 2μm, an OLED working layer with a thickness of 8μm, a second barrier layer with a thickness of 2μm, a polyethylene terephthalate layer with a thickness of 4μm, and a second antistatic layer with a thickness of 2μm.

[0037] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide is 48:53:1.7.

[0038] The raw materials of the first barrier layer and the second barrier layer include: 1.3g cholesterol, 12g phospholipids, 1.2g N-acryloylglycinamide, 1.7g graphene oxide, 0.03g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1.7g hydroxypropyl methylcellulose, 2g polyperfluoroethylene propylene, 4g tetrabutyl titanate, and 1.2g sodium dodecyl sulfate.

[0039] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Cholesterol and phospholipids were added to 18 g of chloroform and stirred evenly. The chloroform was removed by rotary evaporation. The mixture was added to 25 g of deionized water and dispersed evenly. N-acryloyl glycinamide and graphene oxide were added. Ultrasonic dispersion was performed for 25 min at an ultrasonic frequency of 6 kHz. 2,4,6-trimethylbenzoyl-diphenylphosphine oxide was added. The mixture was irradiated with ultraviolet light for 35 min. The mixture was treated with a high-pressure microfluidizer at 13.79 MPa for 3 times. The mixture was dried in a vacuum to obtain pretreated graphene. S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 28 g of 45% ethanol aqueous solution, adjust the pH value of the system to 3-5, ultrasonically treat for 100 minutes, and the ultrasonic frequency is 6 kHz. Use a spray gun to spray on a polystyrene substrate, roll it after drying, and send it into a convection oven. Bake it at a temperature of 135°C for 11 seconds, remove the polystyrene substrate, and cool it to room temperature.

[0040] Example 4 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 30μm and includes: a first antistatic layer with a thickness of 3μm, a first barrier layer with a thickness of 3μm, an OLED working layer with a thickness of 12μm, a second barrier layer with a thickness of 3μm, a polyethylene terephthalate layer with a thickness of 6μm, and a second antistatic layer with a thickness of 3μm.

[0041] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide is 42:57:1.3.

[0042] The raw materials of the first barrier layer and the second barrier layer include: 1.7g cholesterol, 8g phospholipids, 1.8g N-acryloylglycinamide, 1.3g graphene oxide, 0.07g 1-hydroxycyclohexylphenyl ketone, 1.3g hydroxypropyl methylcellulose, 4g polyperfluoroethylene propylene, 2g tetrabutyl titanate, and 1.8g sodium dodecyl sulfate.

[0043] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Cholesterol and phospholipids were added to 12 g of chloroform and stirred evenly. The chloroform was removed by rotary evaporation. The mixture was added to 35 g of deionized water and dispersed evenly. N-acryloyl glycinamide and graphene oxide were added. The mixture was ultrasonically dispersed for 15 min at an ultrasonic frequency of 10 kHz. 1-hydroxycyclohexyl phenyl ketone was added. The mixture was ultraviolet-irradiated for 25 min. The mixture was treated with a high-pressure microfluidizer at 27.58 MPa for 3 times. The mixture was vacuum-dried to obtain pretreated graphene. S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 22 g of 55% ethanol aqueous solution, adjust the pH value of the system to 3-5, ultrasonically treat for 80 minutes, and the ultrasonic frequency is 10 kHz. Use a spray gun to spray on a polystyrene substrate, roll it after drying, and send it into a convection oven. Bake it at a temperature of 125°C for 13 seconds, remove the polystyrene substrate, and cool it to room temperature.

[0044] Example 5 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 25μm and includes: a first antistatic layer with a thickness of 2.5μm, a first barrier layer with a thickness of 2.5μm, an OLED working layer with a thickness of 10μm, a second barrier layer with a thickness of 2.5μm, a polyethylene terephthalate layer with a thickness of 5μm, and a second antistatic layer with a thickness of 2.5μm.

[0045] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide is 45:55:1.5.

[0046] The raw materials of the first barrier layer and the second barrier layer include: 1.5g cholesterol, 10g phospholipids, 1.5g N-acryloylglycinamide, 1.5g graphene oxide, 0.05g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1.5g hydroxypropyl methylcellulose, 3g polyperfluoroethylene propylene, 3g tetrabutyl titanate, and 1.5g sodium dodecyl sulfate.

[0047] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Cholesterol and phospholipids were added to 15 g of chloroform and stirred evenly. The chloroform was removed by rotary evaporation. The mixture was added to 30 g of deionized water and dispersed evenly. N-acryloyl glycinamide and graphene oxide were added. The mixture was ultrasonically dispersed for 20 min at an ultrasonic frequency of 9 kHz. 2,4,6-trimethylbenzoyl-diphenylphosphine oxide was added. The mixture was irradiated with ultraviolet light for 30 min. The mixture was treated with a high-pressure microfluidizer at 20.685 MPa for 3 times. The mixture was vacuum dried to obtain pretreated graphene. S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 25 g of 50% ethanol aqueous solution, adjust the pH value of the system to 3-5, ultrasonically treat for 90 minutes, and the ultrasonic frequency is 9 kHz. Use a spray gun to spray on a polystyrene substrate, roll it after drying, and send it into a convection oven. Bake it at a temperature of 130°C for 12 seconds, remove the polystyrene substrate, and cool it to room temperature.

[0048] Comparative Example 1 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 25μm and includes: a first antistatic layer with a thickness of 2.5μm, a first barrier layer with a thickness of 2.5μm, an OLED working layer with a thickness of 10μm, a second barrier layer with a thickness of 2.5μm, a polyethylene terephthalate layer with a thickness of 5μm, and a second antistatic layer with a thickness of 2.5μm.

[0049] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide is 45:55:1.5.

[0050] The raw materials of the first barrier layer and the second barrier layer include: 1.5g cholesterol, 10g phospholipids, 1.5g N-acryloylglycinamide, 1.5g graphene oxide, 0.05g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1.5g hydroxypropyl methylcellulose, 3g polyperfluoroethylene propylene, 3g tetrabutyl titanate, and 1.5g sodium dodecyl sulfate.

[0051] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1, ultrasonically disperse N-acryloyl glycinamide and graphene oxide for 20 min at an ultrasonic frequency of 9 kHz, add 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, irradiate with ultraviolet light for 30 min, and vacuum dry to obtain pretreated graphene; S2. Add cholesterol and phospholipids to 15g of chloroform and stir evenly. Remove the chloroform by rotary evaporation, add to 30g of deionized water and disperse evenly. Treat with 20.685MPa high-pressure microjet for 3 times, vacuum dry, and then add with pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 25g of 50% ethanol aqueous solution, adjust the pH value of the system to 3-5, ultrasonically treat for 90min, the ultrasonic frequency is 9kHz, use a spray gun to spray on a polystyrene substrate, roll after drying, send into a convection oven, bake at 130℃ for 12s, remove the polystyrene substrate, and cool to room temperature.

[0052] Comparative Example 2 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 25μm and includes: a first antistatic layer with a thickness of 2.5μm, a first barrier layer with a thickness of 2.5μm, an OLED working layer with a thickness of 10μm, a second barrier layer with a thickness of 2.5μm, a polyethylene terephthalate layer with a thickness of 5μm, and a second antistatic layer with a thickness of 2.5μm.

[0053] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide is 45:55:1.5.

[0054] The raw materials of the first barrier layer and the second barrier layer include: 1.5g cholesterol, 10g phospholipids, 1.5g N-acryloylglycinamide, 1.5g graphene oxide, 0.05g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1.5g hydroxypropyl methylcellulose, 3g polyperfluoroethylene propylene, 3g tetrabutyl titanate, and 1.5g sodium dodecyl sulfate.

[0055] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Cholesterol and phospholipids were added to 15 g of chloroform and stirred evenly. The chloroform was removed by rotary evaporation. The mixture was added to 30 g of deionized water and dispersed evenly. N-acryloyl glycinamide and graphene oxide were added. The mixture was ultrasonically dispersed for 20 min at an ultrasonic frequency of 9 kHz. 2,4,6-trimethylbenzoyl-diphenylphosphine oxide was added. The mixture was irradiated with ultraviolet light for 30 min. The mixture was treated with a high-pressure microfluidizer at 20.685 MPa for 3 times. The mixture was vacuum dried to obtain pretreated graphene. S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 25 g of 50% ethanol aqueous solution, adjust the pH value of the system to 3-5, perform ultrasonic treatment for 90 minutes, and set the ultrasonic frequency to 9 kHz. Use a spray gun to spray on a polystyrene substrate, roll it after drying, remove the polystyrene substrate, and cool it to room temperature.

[0056] Comparative Example 3 The ultra-high water and oxygen barrier film for automotive OLED display products has a thickness of 25μm and includes: a first antistatic layer with a thickness of 2.5μm, a first barrier layer with a thickness of 2.5μm, an OLED working layer with a thickness of 10μm, a second barrier layer with a thickness of 2.5μm, a polyethylene terephthalate layer with a thickness of 5μm, and a second antistatic layer with a thickness of 2.5μm.

[0057] The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide; the mass ratio of linear low-density polyethylene, low-density polyethylene and ethoxylated lauramide is 45:55:1.5.

[0058] The raw materials of the first barrier layer and the second barrier layer include: 1.5g cholesterol, 10g phospholipids, 1.5g N-acryloylglycinamide, 1.5g graphene oxide, 0.05g 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 1.5g hydroxypropyl methylcellulose, 3g polyperfluoroethylene propylene, 3g tetrabutyl titanate, and 1.5g sodium dodecyl sulfate.

[0059] The first barrier layer and the second barrier layer are prepared by the following specific steps: S1. Cholesterol and phospholipids were added to 15 g of chloroform and stirred evenly. The chloroform was removed by rotary evaporation. The mixture was added to 30 g of deionized water and dispersed evenly. Graphene oxide was added and ultrasonically dispersed for 20 min at an ultrasonic frequency of 9 kHz. The mixture was treated with a high-pressure microfluidizer at 20.685 MPa for 3 times and vacuum dried to obtain pretreated graphene. S2. Mix N-acryloylglycinamide with 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, irradiate with ultraviolet light for 30 minutes, then add it with pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and sodium dodecyl sulfate to 25g of 50% ethanol aqueous solution, adjust the pH value of the system to 3-5, ultrasonically treat for 90 minutes, and the ultrasonic frequency is 9kHz. Use a spray gun to spray on a polystyrene substrate, roll it after drying, and send it into a convection oven. Bake it at 130°C for 12 seconds, remove the polystyrene substrate, and cool it to room temperature.

[0060] The barrier properties of the ultra-high water and oxygen barrier films for vehicle-mounted OLED display products obtained in Example 5 and Comparative Examples 1-3 were measured, as follows: The water vapor permeability test was carried out according to the weight gain method in GB / T 1037-2021 "Determination of Water Vapor Permeability of Plastic Film and Sheeting - Cup Weight Gain and Weight Loss Method". The test temperature was 38°C, the humidity was 90%RH, the preheating time was 2h, the rotation interval was 10min, and 3 parallels were set for each group.

[0061] The oxygen transmission rate test was carried out according to GB / T 1038.1-2022 "Plastic film and sheet gas permeability test method Part 1: Differential pressure method", the test temperature was 23°C, the humidity was 50%RH, and the vacuum time was 4h. Ensure that the sample surface is free of pollution and scratches, and set 3 parallels for each group.

[0062] like Figure 2 As shown, the water vapor permeability and oxygen permeability of the ultra-high water-oxygen barrier film for vehicle-mounted OLED display products obtained in Example 5 are the lowest, which is significantly better than those of Comparative Examples 1-3 (P < 0.01), confirming that the ultra-high water-oxygen barrier film for vehicle-mounted OLED display products obtained in Example 5 has the best barrier performance.

[0063] The vehicle-mounted OLED display products obtained in Example 5 and Comparative Examples 1-3 were paved on the surface of a glass slide with an ultra-high water and oxygen barrier film, and 5 μL of water droplets were added to measure the static contact angle.

[0064] Example 5 and Comparative Examples 1-3 were assembled after the OLED working layer was removed, that is, each group of samples consisted of a first antistatic layer with a thickness of 2.5 μm, a first barrier layer with a thickness of 2.5 μm, a second barrier layer with a thickness of 2.5 μm, a polyethylene terephthalate layer with a thickness of 5 μm, and a second antistatic layer with a thickness of 2.5 μm. The tensile strength of each group of samples was tested with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for thin plastics and sheets".

[0065] like Figure 3As shown, the static water contact angle and tensile strength of the ultra-high water and oxygen barrier film for vehicle-mounted OLED display products obtained in Example 5 are both the highest, which are better than those of Comparative Examples 1-3 (P < 0.05). However, the static water contact angle and tensile strength of the ultra-high water and oxygen barrier film for vehicle-mounted OLED display products obtained in Comparative Example 2 are both the lowest, which are inferior to those of Example 5 and Comparative Examples 1-2 (P < 0.05).

[0066] The thermal stability of the ultra-high water and oxygen barrier films for vehicle-mounted OLED display products obtained in Example 5 and Comparative Examples 1-3 was tested by a thermal analyzer, the temperature range was 25-600° C., the protective atmosphere was nitrogen, and the heating rate was 20° C. / min.

[0067] like Figure 4 As shown, the thermal decomposition temperature and final residual rate of the ultra-high water and oxygen barrier film for vehicle-mounted OLED display products obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-3 (P < 0.05).

[0068] The applicant believes that the reason for the above results is that in the barrier layer used in the present invention, cholesterol and phospholipids are used to form a phospholipid vesicle double-layer structure, and N-acryloyl glycinamide and graphene oxide are bonded to the hydrophilic outer layer of the double-layer structure through hydrogen bonds. After initiation, the two are combined in the outer layer of the phospholipid vesicle, which not only has good barrier performance and effectively reduces the influence of water vapor and oxygen, but also the multiple hydrogen bond structure formed after the combination can make the barrier layer have good self-healing properties. The thin film formed by spraying on the substrate with a spray gun can be effectively wrinkled after rolling and heating, which can cooperate with the effect of micron-sized silica particles to achieve a significant superhydrophobic effect. In the present invention, a barrier layer is arranged between the first antistatic layer and the OLED working layer, and between the OLED working layer and the PET layer, which can not only significantly prolong the penetration path and penetration time of water and oxygen molecules in the barrier layer, but also the nanoparticles and the stable pleated structure have excellent moisture barrier effect. The super-hydrophobic structure layer can exist stably and has excellent barrier performance, thereby increasing the service life of the entire water and oxygen barrier film. At the same time, the antistatic layer and the PET layer work synergistically, so that the obtained product has extremely high structural stability, is suitable for various OLED flexible panels, has a simple structure, and is easy to use.

[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Ultra-high water and oxygen barrier film for automotive OLED display products, characterized in that: The thickness is 15-35 μm, and it includes in sequence: a first antistatic layer, a first barrier layer, an OLED working layer, a second barrier layer, a polyethylene terephthalate layer, and a second antistatic layer; The thickness ratio of the first antistatic layer, the first barrier layer, the OLED working layer, the second barrier layer, the polyethylene terephthalate layer, and the second antistatic layer is 2-4: 2-4: 8-16: 2-4: 4-8: 2-4.

2. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 1, characterized in that: The raw materials of the first antistatic layer and the second antistatic layer both include: linear low-density polyethylene, low-density polyethylene and antistatic agent; the mass ratio of linear low-density polyethylene, low-density polyethylene and antistatic agent is 40-50:50-60:1-2.

3. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 2, characterized in that: The antistatic agent is ethoxylated alkyl amide and / or ethoxylated lauryl amide.

4. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 1, characterized in that: The raw materials of the first barrier layer and the second barrier layer include, by mass, 1-2 parts of cholesterol, 5-15 parts of phospholipids, 1-2 parts of N-acryloylglycinamide, 1-2 parts of graphene oxide, 0.01-0.1 parts of photoinitiator, 1-2 parts of hydroxypropyl methylcellulose, 1-5 parts of polyperfluoroethylene propylene, 1-5 parts of tetrabutyl titanate, and 1-2 parts of surfactant.

5. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 1, characterized in that: The first barrier layer and the second barrier layer are both prepared by the following specific steps: S1. Add cholesterol and phospholipids to chloroform and stir evenly, remove chloroform by rotary evaporation, add to deionized water and disperse evenly, add N-acryloyl glycinamide and graphene oxide, ultrasonically disperse for 10-30 minutes, add photoinitiator, ultraviolet irradiation for 20-40 minutes, high-pressure microfluidization treatment for 2-4 times, and vacuum dry to obtain pretreated graphene; S2. Add pretreated graphene, hydroxypropyl methylcellulose, polyperfluoroethylene propylene, tetrabutyl titanate, and surfactant to an ethanol aqueous solution, adjust the pH value of the system to 3-5, perform ultrasonic treatment for 1-2 hours, spray on the substrate using a spray gun, roll after drying, bake at 120-140°C for 10-15 seconds, remove the substrate, and cool to room temperature.

6. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 5, characterized in that: In S1, the ultrasound frequency is 5-12kHz.

7. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 5, characterized in that: In S1, the pressure of the high-pressure microfluidization treatment was 6.895-34.475 MPa.

8. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 5, characterized in that: In S1, the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

9. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 5, characterized in that: In S2, the surfactant is sodium dodecyl sulfate.

10. The ultra-high water and oxygen barrier film for vehicle-mounted OLED display products according to claim 5, characterized in that: In S2, the ultrasound frequency is 5-12kHz.

Citation Information

Patent Citations

  • Biosensor interface constructed through phospholipid membrane layer and preparation method of interface

    CN105067801A

  • Comprehensive functional membrane, manufacturing method thereof, and OLED display panel

    CN105655501A

  • Self-repair conductive hydrogel based on multiple hydrogen bonding and preparation method thereof

    CN108484808A

  • Anti-static polyethylene sheet and preparation method thereof

    CN109135035A

  • Water-oxygen barrier film structure for flexible OLED package

    CN109830615A

Cited By

  • Preparation process of recoverable liquid-washing small packaging film

    CN120206939A